Does Cardiorespiratory Fitness Influence the Effect of Acute Aerobic Exercise on Executive Function? - Cui, Jie; Zou, Liye; Herold, Fabian; Yu, Qian; Jiao, Can; Zhang, Yanjie; Chi, Xinli; Müller, Notger G.; Perrey, Stephane; Li, Lin; Wang, Chenbo (Frontiers in Human Neuroscience, 2020)
Background: The beneficial effects of acute exercise on executive function have been well-documented, but the influence of cardiorespiratory fitness on this effect requires further investigations, especially using imaging technique. This study aimed to examine the effects of cardiorespiratory fitness on acute exercise-induced changes on behavioral performance and on functional brain activation. Method: Based on their cardiorespiratory fitness level, 62 participants ranked in the top and bottom of the maximum oxygen consumption (VO2 max) were finally selected and allocated to high-fit group or low-fit group. Both groups were asked to complete the Stroop task after 30 minutes of aerobic exercise and chair-seated rest (control session). Among them, 26 participants were randomly selected and were asked to undergo the Functional Magnetic Resonance Imaging (fMRI). Results: Behavioral results showed that individuals responded significantly faster after exercise than those in the control session. The fMRI results revealed a significant interaction effects of Group by Session in brain regions including anterior cingulate cortex (ACC) and bilateral dorsal lateral prefrontal cortex (DLPFC). For the ACC, activation in the high-fit group was significantly decreased after aerobic exercise compared to those in the control session; whereas an increased activation was noticed in the low-fit group. Regarding to the bilateral DLPFC, activation in high-fit group was significantly decreased after exercise compared to those in the control session, while no significant differences were found in the low-fit group. In addition, for the post-exercise session a significant positive correlations between activation of the ACC and left DLPFC in the high-fit group was observed. There was a significant negative correlation between activation of the anterior cingulate cortex and reaction time in the congruent condition after exercise in the low-fit group. Conclusions: Findings further clarify the neurophysiological processes of acute exercise-induced changes in cognitive performance as they suggest that cardiorespiratory fitness is an important factor which influences changes in brain activation patterns in response to acute aerobic exercises.